Comparison of harvesting productivity, cost, and residual stand damages between single-tree selection thinning and mechanized line thinning using a small-scale grapple-saw. Issue 2 (3rd April 2022) - Cho, Min-Jae; Choi, Yun-Sung; Oh, Jae-Heun; Mun, Ho-Seong; Han, Sang-Kyun
Abstract: Considerable amounts of noncommercial materials generated from thinning treatments remain unattended on the site because the value of small-sized timber is lower than overall thinning operation costs in South Korea. In addition, thinning operations with conventional and mechanized harvesting systems often cause severe physical damage to residual trees. In this study, therefore, we compared and analyzed the harvesting productivity, cost, and residual stand damage between single-tree selection thinning (SST) and mechanized line thinning (MLT) systems on conifer plantation forests. For conventional SST, ground skidding (uphill/downhill) was performed using a tractor winch after manual felling and bucking. The MLT consisted of mechanized felling, downhill shovel logging, and processing with a small-scale grapple-saw for the fourth double row (MLT1) and the third row (MLT2) thinning section. The MLT system was more productive and cost-effective in performing thinning treatment and collecting thinning materials than SST. The MLT1 and MLT2 costs were 81.4% and 70.6% lower than the SST cost (77.6/m 3 ), respectively. The residual stand damages of the SST (3.4%) were lower than those of MLT1 (4.8%) and MLT2 (21.2%); however, there was no significant difference in residual stand damages between two thinning systems ( p > 0.05). Therefore, forest managers should consider the use of MLT system to reduce thinning costs and efficiently produce thinning materials for their thinning operations. However, operators still need to be careful felling and extracting operations to reduce the residual stand damages for thinning treatments.